2021
DOI: 10.1111/jon.12925
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous trigeminal tractotomy for trigeminal neuralgia: Postoperative MRI findings

Abstract: Background and Purpose: Percutaneous trigeminal tractotomy is an ablative procedure that can be used to treat trigeminal neuralgia in patients who have failed prior pharmacologic and surgical treatments. Using perioperative computed tomography (CT) guidance, ablation of the descending spinal trigeminal nucleus and trigeminal tract can be performed precisely to mitigate damage to surrounding structures. These patients are subsequently followed with postoperative imaging and clinical visits to assess long-term p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Available postoperative MRI data in our patients do not allow us to draw definitive conclusions about long-term postoperative outcomes of the surgery since not all patients had neuroimaging completed. Gurbani et al [34] after analyzing the postoperative images of 4 patients who underwent transcutaneous nucleotractotomy, concluded that the ablation zone when performing this procedure according to the standard method corresponds to the anatomical location of the nucleus and tract of the trigeminal nerve. The availability of visualization techniques for the spinal nucleus of the trigeminal nerve will make it possible to identify individual differences in the electrode location during destruction [35].…”
Section: Resultsmentioning
confidence: 99%
“…Available postoperative MRI data in our patients do not allow us to draw definitive conclusions about long-term postoperative outcomes of the surgery since not all patients had neuroimaging completed. Gurbani et al [34] after analyzing the postoperative images of 4 patients who underwent transcutaneous nucleotractotomy, concluded that the ablation zone when performing this procedure according to the standard method corresponds to the anatomical location of the nucleus and tract of the trigeminal nerve. The availability of visualization techniques for the spinal nucleus of the trigeminal nerve will make it possible to identify individual differences in the electrode location during destruction [35].…”
Section: Resultsmentioning
confidence: 99%
“…The patient returned to baseline pain levels at 1 month post-tractotomy [14]. Anisimov et al presented a case with minimal pain reduction (VAS reduction from 10 to 8) after percutaneous nucleotractotomy for deafferentiation pain following a surgical attempt to treat trigeminal neuralgia [15]. While Kanpolat et al reported an 80% success rate based on VAS scores in their series of failure trigeminal neuralgia patients, the long-term outcomes were not specified.…”
Section: Discussionmentioning
confidence: 99%
“…Три пациента отметили улучшение в виде купирования болевого синдрома. Опасность данной процедуры обусловлена тем, что оперативное вмешательство проводится на стволе головного мозга, что требует технического оснащения и высокой квалификации хирурга [52].…”
Section: хирургическое лечениеunclassified